Hydraulic Coagulation–Ultrafiltration for Peat Water in South Kalimantan - Sulaiman Hamzani; Syarifudin A; Fatmi Indah Hati; Tien Zubaidah (Gema Lingkungan Kesehatan, 2026)
Access to safe drinking water remains a critical public health challenge in South Kalimantan, where peat-influenced water sources exhibit high turbidity, elevated iron concentrations, and acidic pH. This experimental study designed, fabricated, and evaluated a Circular Pipe–Synthetic Ultrafiltration (CP-SKU) device a hydraulic coagulation reactor requiring no mechanical energy input — for treatment of peat-influenced dug well water. Five sequential treatment configurations were tested in triplicate using PAC Powder (100 mg/L) as coagulant. The CP-SKU configuration achieved the best performance: turbidity reduction from 19.8 to 0.47 NTU (97.63%), iron below detection limit (<0.1 mg/L), and pH 6.72 — all compliant with Indonesian Ministry of Health Regulation No. 2 of 2023. Extended trials on high-turbidity raw water (83.67 NTU) confirmed 98% turbidity removal and 99.55% MPN Coliform reduction. However, effluent pH (6.39) fell marginally below the 6.5 regulatory threshold, and residual coliform indicators did not meet zero-tolerance standards, necessitating upstream pH correction and downstream disinfection prior to consumption.